The impact of RBV on value creation in the pharmaceutical industry - Santos, T. F. dos.; Pereira, A.; Correia, R.; Geraldes, J.; Gonçalves, R.; Lopes da Costa, R. (International Journal of Management and Decision Making, 2025)
The theory of the resource-based view addresses all the complexity of adopting strategic methods in competitive environments, such as the pharmaceutical industry, in which there is a constant struggle to acquire competitive advantage and for companies to differentiate themselves from others. Having said this, it is important to understand the impact that the resource-based view can have on the pharmaceutical industry, and how it can generate competitive advantage for different companies. The methodology for data collection was the realisation of semi-structured interviews based on questions that emerged throughout the literature review, where the MAXQDA software was used for analysis and coding of the corpus of each interview. It was concluded that this type of strategy has several positive impacts at the internal and external levels of the pharmaceutical industry, ranging from the creation of more competitive environments through the success of innovation, the allocation of resources in the best way to meet the needs of the company and the market, and clearly a greater internal knowledge of the weaknesses of each company, investing in continuous improvement.